"We belong to nature and nature belongs to us": Ensuring transhumance during the Covid-19 pandemic. Issue 1 (2nd January 2022) - Majeed, Bhat Iqball
ABSTRACT: The exponential emergence of the Covid-19 pandemic, with such an intensity on a global scale, created fear, paranoia, and insecurity among populations across the world. The Worldometer Website operated by Dadax, which provides live statistics of Covid-19, showed a daily increase in the number of people infected by this "strange" virus that shackled even the most powerful governments of the world. Nationwide lockdowns imposed by all the giant economic powers and administrations of various countries completely ceased any mobility of the people. However, despite all this, one of the most vulnerable groups was the nomads, whose mobility is the essence as well as a prerequisite for their existence. The Bakkarwals of Jammu and Kashmir (India), a nomadic community, showed exemplary courage amid all the chaos by undertaking their transhumant movement, walking 300 kilometers with their livestock and children to reach the pastures. The pandemic-era story of this marginalized and neglected population is worth telling.